FAMILY FIRM PERFORMANCE IN CENTRAL KALIMANTAN: THE ROLE OF SOCIOEMOTIONAL WEALTH AND MANAGERIAL CAPABILITIES - Marchyta, Nony Kezia; Susanto, Agustinus Willi; Susilo, Clarissa Listya; Hendra, Hendra (ITB AAS Indonesia Surakarta, 2024)
This research investigates the critical role of family companies in the rapid expansion of MSMEs in Central Kalimantan. This research examines the effect of socioemotional wealth on firm performance with managerial capabilities as a mediating variable. The concept of socioemotional wealth is a concept that is still rarely studied in family companies and makes family companies a unique entity. This research is classified as quantitative research using primary data. The sampling technique used purposive sampling, with 63 family company owners in Central Kalimantan, Indonesia, as the research sample. The results obtained show a positive influence of socioemotional wealth on firm performance. Socioemotional wealth has a positive effect on managerial capabilities, and there is a partial mediation effect on the role of managerial capabilities as a mediating variable. The results also show a positive influence of managerial capabilities on firm performance.